Ladies in the Laboratory? American and British Women in Science, 1800-1900: A Survey of Their Contributions to Research - Creese, Mary R.S. (Rowman & Littlefield Publishers, 2000)
A systematic survey and comparison of the work of 19th-century American and British women in scientific research, this book covers the two countries in which women of the period were most active in scientific work and examines all the fields in which they were engaged. The field-by-field examination brings out patterns and concentrations in women's research (in both countries) and allows a systematic comparison of the two national groups. Through this comparison, new insights are provided into how the national patterns developed and what they meant, in terms of both the process of women's entry into research and the contributions they made there. Ladies in the Laboratory? features a specialized bibliography of nineteenth century research journal publications by women, created from the London Royal Society's Catalogue of Scientific Papers, 1800-1900. In addition, 23 illustrations present in condensed form information about American and British women's scientific publications throughout the nineteenth century. This well-organized blend of individual life stories and quantitative information presents a great deal of new data and field-by-field analysis; its broad and methodical coverage will make it a basic work for everyone interested in the story of women's participation in nineteenth century science.